Synthesis of some new 4-oxo-thiazolidines, tetrazole and triazole derived from 2-SH-benzothiazole and antimicrobial screening of some synthesized - Suaad M.H. Al-Majidi (Journal of Saudi Chemical Society)
A new heterocyclic derivative of 2-mercaptobenzothiazole (MBT) comprising 4-oxothiazolidines, tetrazole and triazole, through the reaction of (MBT) with hydrazine hydrate obtained 2-hydrazobenothiazol (1), which was condensed with various aromatic aldehydes. Azomethine derivatives (2a–c) are converted into a number of 4-oxothiazolidines (3a–c) and tetrazole derivatives (4a–c), through the reaction of azomethine derivatives (2a–c) with mercaptoacetic acid and sodium azide, respectively. Also the reaction of compound (1) with triethylorthoformate and nitrous acid to produce the corresponding (triazole and tetrazole) benzothiazole (5,6) was reported. Triazole moieties reported condensation (MBT) with ethylbromo acetate and potassium hydroxide by the fusion method and resulted in ester-2-mercaptobenzothiazole (7), which was treated with hydrazine hydrate to give a hydrazine derivative (8), then converting these compounds (8) to phenyl semicarbazide (9) and phenyl thiosemicarbazide (10) derivatives. Cyclization compounds (9,10) in alkaline media (4 N·NaOH) gave triazoles compounds (11,12). Furthermore the compound (8) was converted to the dithiocarbazate salt (13) which was then cyclized with hydrazine hydrate to give substituted triazole (14). The prepared compounds were identified by spectral methods (FTIR, 1H NMR, 13C NMR) and some of its physical properties were measured and furthermore the effects of the preparing compounds on some strains of bacteria were studied.